Ambidexterity in Social Capital, Dynamic Capability, and SMEs’ Performance: Quadratic Effect of Dynamic Capability and Moderating Role of Market Orientation - Zhou, Luanping; Peng, Michael Yao-Ping; Shao, Lijin; Yen, Hsin-Yi; Lin, Ku-Ho; Anser, Muhammad Khalid (Frontiers in Psychology, 2021)
The importance of organizational ambidexterity was stressed in different fields of management. This study was using a distinct method to measure the differences in the degree of ambidexterity to bridge the gap with the previous studies and to provide more insights in the successful management of exploitation and exploration. This study surveyed Taiwanese SMEs to test the hypotheses. We issued 1000 questionnaires in total and received 234 valid ones. Results indicate exploitative and explorative capabilities exerting non-linear effect on performance. Likewise, ambidexterity and its interaction with market orientation have positive influence on firm performance. This study used structural equation modeling to analyze data, as this approach is known to be particularly advantageous for the exploratory nature of this study. We also used hierarchical regression analysis to test interaction and moderating effects. The study contributes to the literature in two ways. First, we offer a clearer understanding of the complete concept of social capital, including inter-firm and intra-firm social capital, and how contributes to improving and extending existing exploitative capabilities. Second, this study outlines how market orientation can have different effects on an ambidextrous strategy that is adopted to improve Taiwanese SMEs performance.